Labour market differences between immigrant and UK-born employees: What is the role of employers? - Kaya, Ezgi (International Journal of Population Data Science, 2025)
Objectives This study aims to investigate the role of employers in labour market disparities between UK-born and immigrant employees using data from the newly linked Annual Survey of Hours and Earnings - 2011 Census for England and Wales. It explores various labour market outcomes, identifying both employer-specific effects and within-employer inequalities. Methods The analysis employs well-established regression and decomposition methods to investigate labour market disparities between UK-born and immigrant employees in outcomes such as pay, working hours, occupational skill levels, and temporary employment. Employer-specific effects are incorporated to examine the role of differential sorting of employees across employers and within-employer inequalities. The dataset’s unique employer-employee linked structure enables a precise estimation of the extent to which disparities arise from differences in where immigrant and UK-born employees work versus within-employer dynamics. This approach provides a detailed understanding of how employers’ hiring and pay-setting practices contribute to labour market inequalities. Results We find that immigrants earn less, work longer hours, and are more likely to hold low-skilled or temporary jobs compared to UK-born employees. Adjusting for employee characteristics such as education and work region narrows, but does not eliminate, these gaps, highlighting persistent disparities. Employer-specific effects further reduce the gaps, suggesting that differences in where immigrant and UK-born employees work partly explain the disparities. However, within-employer inequalities persist between comparable immigrant and UK-born employees, with gaps of 2.4% in hourly pay, 3.3% in weekly hours, and 5.9% and 1.8% in low-skilled and temporary employment, respectively. These findings highlight the dual role of employers in shaping labour market inequalities through differential sorting of employees and within-employer practices. Conclusion Exploiting the unique features of a linked administrative dataset, this study offers novel insights into labour market disparities between immigrant and UK-born employees by highlighting the role of employers. Our findings suggest that addressing these disparities requires policies targeting both employers' hiring decisions and pay-setting practices.